Perencanaan persediaan obat dengan metode analisis ABC-VEN di Instalasi Farmasi RS “Y” Kota Palopo - Annizha Nurul Fatimah Agus; Chitra Astari; Hurria (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: ABC-VEN analysis is a effective method for evaluating drug needs because it can determine priority drug planning based on cost and therapy. However, not all Pharmacy Installation have implemented this method, one of that is The Pharmacy Installation of “Y” Hospital in Palopo City. Objective: To evaluate drug planning at Pharmacy Installation of “Y” Hospital using the ABC-VEN analysis so that, the investment value for drug procurement is suitable with the budget and meets drug needs in the hospital. Methods: The research is combining qualitative and quantitative approaches. The instruments used are the form of data collection sheets for drug use for the period September-November 2022 and interview guidelines. Results:Out of a total of 626 drug items used in September-November 2022, 11%, 81%, 9% of drug items were included in the priority, main, and additional categories which spent the budget respectively 17%, 81% and 2% of total budget. Conclusion: With the application of the ABC-VEN analysis method, the drug supply budget can be saved by reducing the number of drugs or substituting drugs by finding suppliers that offer lower prices, especially in the NA, NB, and NC categories.